2018
DOI: 10.1002/14651858.cd003303.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Reading aids for adults with low vision

Abstract: Editorial group: Cochrane Eyes and Vision Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 4, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 64 publications
0
71
0
4
Order By: Relevance
“…A Cochrane Review concluded that electronic devices tended to be preferred to optical ones. 5 More recently, a retrospective review by Nguyen et al 22 of 530 vision rehabilitation patients reported improved reading speeds in patients who were prescribed low vision aids; 42% of the group received video camera magnifiers. It is not stated whether there was a difference between those receiving video camera magnifiers or other aids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane Review concluded that electronic devices tended to be preferred to optical ones. 5 More recently, a retrospective review by Nguyen et al 22 of 530 vision rehabilitation patients reported improved reading speeds in patients who were prescribed low vision aids; 42% of the group received video camera magnifiers. It is not stated whether there was a difference between those receiving video camera magnifiers or other aids.…”
Section: Discussionmentioning
confidence: 99%
“…A 2013 Cochrane Review examined all available randomized and quasi-randomized studies relevant to magnifying reading aids for adults with low vision (10 studies were included) and concluded that the evidence was insufficient to assess the effect of low-vision devices on reading performance, although there was some evidence that electronic devices were associated with more improvement in reading speed than optical devices were. 5 The present study compared patients who received standard visual rehabilitation (VR) with those who, in addition to VR, were provided with a video magnifier (VM) at their initial contact with a multidisciplinary vision rehabilitation service. VR included an initial consultation during which patients were educated about rehabilitation strategies, given information about remaining visual function, and shown a range of optical and electronic devices, which they could purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the provision of magnifiers and/or teaching patients the techniques of eccentric viewing are almost always the first two steps in addressing the reading goal of patients with macular disease. Comprehensive reviews on these two topics can be found elsewhere . In this paper, we will focus on other attempts to improve reading performance which included modifications of current fonts and/or designs of new fonts that might make reading easier, training or perceptual learning to improve reading performance, and remapping the visual input that fall into the scotoma onto a more functional part of the retina.…”
Section: Improving Reading For People With Macular Diseasementioning
confidence: 99%
“…To determine the benefits of reading rehabilitation, appropriate outcome measures are needed. Reading speed is often used as an outcome measure (Virgili et al, 2018), since it is a good predictor of visual difficulty (Hazel, Petre, Armstrong, Benson, & Frost, 2000;McClure, Hart, Jackson, Stevenson, & Chakravarthy, 2000). The ability to read print of different sizes is also of practical importance (Legge and Bigelow, 2011), and measures of reading acuity (RA; the smallest size of print that can be read) and critical print size (CPS; the smallest size of print that can be read at maximum reading speed (MRS)) can indicate whether someone would be able to read print of a specific size.…”
Section: Introductionmentioning
confidence: 99%